Analisis Kemampuan Berpikir Kreatif Siswa Pada Soal Open Ended Materi Pecahan Kelas VII SMP Negeri 16 Palembang (Universitas Muhammadiyah Palembang, 2022)
This study aims to determine students' creative thinking skills in solving open ended mathematics questions in class VII SMP Negeri 16 Palembang. This research approach uses a descriptive research type with a qualitative research type. The population in this study were all students of class VII SMP Negeri 16 Palembang with the sample in this study being students of class VII.8 who carried out learning from the network or online, namely VI.B as many as 23 students. The data collection technique in this study was in the form of a test which served as the main data in this study. Data analysis aims to determine students' creative thinking abilities in solving open ended questions for class VII SMP Negeri 16 Palembang on fractions. After conducting research, the results of this study were obtained with the results of differences in each indicator of fluency, flexibility, and elaboration. Students' thinking ability on the fluency indicator has a score of 53.21, students' thinking ability on the flexibility indicator has a value of 56.34, and students' thinking ability on the elaboration indicator has a value of 91.13. Based on the results of the study, it was obtained that the ability to think creatively was in the sufficient category of 69.56%, the less category was 17.39%, and the category was not 13.04%.